MANAGEMENT OF RECURRENT APHTHOUS STOMATITIS WITH PSYCHOLOGICAL STRESS (Case Report) - Ayu Mashartini Prihanti; Dyah Indartin Setyowati; Leni Rokhma Dewi (UPT Penerbitan Universitas Jember, 2022)
Recurrent aphthous stomatitis (RAS) is an inflammation of the soft tissues of the mouth characterized by recurrent ulcers in the absence of other underlying diseases. Pain and discomfort in the area around the ulcer can be caused by mastication, or during speech. The characteristics of RAS are in the form of recurrent ulcers in the oral cavity with a round or oval shape and edges surrounded by erythema with a gray-yellow base of the lesion. RAS occurs starting at a young age, namely children and puberty, and can occur in adults. RAS is clinically divided into 3 types, namely major, minor, and herpetiform. A 21-year-old female patient came to the RSGM Universitas Jember with complaints of stomatitis in the mouth. Canker sores recur at least 1 year 3-5 times, and usually heal on their own in about 10 days. Intra-oral examination of the lower and lateral labial mucosa of the right tongue found ulcers, round, 2-3mm in diameter, white center, erythematous edges, clear boundaries. Based on the examination, the patient was diagnosed with Minor Recurrent Aphthous Stomatitis with a predisposition to psychological stress. The patient was given topical anti-inflammatory aloe vera therapy with multivitamin becomzet (vitamin B complex, A, C, E, and Zinc). The patient showed a positive response to the therapy.